2021
DOI: 10.3390/antibiotics10091080
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Antibiotic Resistance among Opportunistic Pathogens Isolated from Patients with COVID-19 under Mechanical Ventilation: Results of a Single-Center Study

Abstract: The effect of the COVID-19 pandemic on antibiotic resistance diffusion in healthcare settings has not been fully investigated. In this study we evaluated the prevalence of antibiotic resistance among opportunistic pathogens isolated from patients with COVID-19 under mechanical ventilation. An observational, retrospective, analysis was performed on confirmed cases of COVID-19 patients who were admitted to the ICU department of S. Salvatore Hospital in Pesaro, Italy, from 1 February 2021 to 31 May 2021. We consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 24 publications
1
20
0
1
Order By: Relevance
“…They detected a high prevalence of A . baumannii Carbapenem-resistant colonization with an infection rate of 75% [ 29 ]. Based on our findings, Acinetobacter spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They detected a high prevalence of A . baumannii Carbapenem-resistant colonization with an infection rate of 75% [ 29 ]. Based on our findings, Acinetobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…faecium were the most common species. Also, E. faecium showed to be MDR in 71.4% of the patients [ 29 ]. Moreover, emergence of Candida spp.…”
Section: Discussionmentioning
confidence: 99%
“…Temperoni et al [ 27 ] showed a 64.5% rate of MDR microorganisms in patients admitted in the ICU setting. Our data enormously differ from theirs, as we only highlighted nine MDR Gram-negative pathogens over 88 infectious events (10.2%).…”
Section: Discussionmentioning
confidence: 99%
“…Our data enormously differ from theirs, as we only highlighted nine MDR Gram-negative pathogens over 88 infectious events (10.2%). However, this difference is justified by the fact that Temperoni’s study only reports data regarding 89 ICU patients, while in our case we also included patients from other wards [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation